2001
DOI: 10.1096/fj.00-0629fje
|View full text |Cite
|
Sign up to set email alerts
|

Space shuttle flight (STS‐90) enhances degradation of rat myosin heavy chain in association with activation of ubiquitin‐proteasome pathway

Abstract: To elucidate the mechanisms of microgravity‐induced muscle atrophy, we focused on fast‐type myosin heavy chain (MHC) degradation and expression of proteases in atrophied gastrocnemius muscles of neonatal rats exposed to 16‐d spaceflight (STS‐90). The spaceflight stimulated ubiquitination of proteins, including a MHC molecule, and accumulation of MHC degradation fragments in the muscles. Semiquantitative reverse transcriptase‐polymerase chain reaction revealed that the spaceflight significantly increased mRNA l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
169
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 162 publications
(187 citation statements)
references
References 47 publications
17
169
0
Order By: Relevance
“…It is reported that the ubiquitin-dependent proteolytic pathway causes the microgravity induced muscular atrophy, and micro-array data indicates the up-regulation of the expression of ubiquitin ligases in the space-flown rat (Ikemoto et al, 2001;Nikawa et al, 2004). In our data, body-wall muscle of unc-15(e73) animal occurred atrophy after spaceflight (Fig.…”
Section: Alteration Of Thick Filament Protein Amounts After Microgravsupporting
confidence: 59%
“…It is reported that the ubiquitin-dependent proteolytic pathway causes the microgravity induced muscular atrophy, and micro-array data indicates the up-regulation of the expression of ubiquitin ligases in the space-flown rat (Ikemoto et al, 2001;Nikawa et al, 2004). In our data, body-wall muscle of unc-15(e73) animal occurred atrophy after spaceflight (Fig.…”
Section: Alteration Of Thick Filament Protein Amounts After Microgravsupporting
confidence: 59%
“…Recent investigations have indicated that the three primary proteolytic systems may work as partners during muscle proteolysis (17,55). The ubiquitin-proteasome pathway appears responsible for degradation of the bulk of proteins, mainly myofibrillar proteins, in conditions of decreased muscle use (55,88,89). However, there is an extensive consensus that intact myofibrillar proteins cannot be degraded by the proteasome (90); consequently, the initial cleavage of myofibrillar proteins requires other proteases (87).…”
Section: 2) Regulation Of Protein Degradationmentioning
confidence: 99%
“…In recent years, free radicals have been implicated as important modulators of biological processes, particularly with respect to processes involved in the regulation of skeletal and cardiac muscle mass [5][6][7][8]. Oxidative stress is characterized by an imbalance between the production of reactive oxygen/nitrogen species and their neutralization through antioxidant defence systems [9].…”
Section: Introductionmentioning
confidence: 99%